Computer security handbook - Bosworth, Seymour; Kabay, Michel E.; Whyne, Eric, 1981- (Hoboken, New Jersey : Wiley, 2014)
Computer security touches every part of our daily lives from our computers and connected devices to the wireless signals around us. Breaches have real and immediate financial, privacy, and safety consequences. This handbook has compiled advice from top professionals working in the real world about how to minimize the possibility of computer security breaches in your systems. Written for professionals and college students, it provides comprehensive best guidance about how to minimize hacking, fraud, human error, the effects of natural disasters, and more. This essential and highly-regarded r.
2.12 SPAM 22.12.1 1994: Green Card Lottery Spam; 2.12.2 Spam Goes Global; 2.13 DENIAL OF SERVICE; 2.13.1 1996: Unamailer; 2.13.2 2000: MafiaBoy; 2.14 HACKER UNDERGROUND; 2.14.1 1981: Chaos Computer Club; 2.14.2 1982: The 414s; 2.14.3 1984: Cult of the Dead Cow; 2.14.4 1984: 2600: The Hacker Quarterly; 2.14.5 1984: Legion of Doom; 2.14.6 1985: Phrack; 2.14.7 1989: Masters of Deception; 2.14.8 1990: Operation Sundevil; 2.14.9 1990: Steve Jackson Games; 2.14.10 1992: L0pht Heavy Industries; 2.14.11 2004: Shadowcrew; 2.14.12 Late 2000s: Russian Business Network (RBN); 2.14.13 Anonymous.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on April 24, 2014).
Keywords: Electronic data processing departments -- Security measures; Computer security; Data protection; Electronic data processing departments -- Security measures; Information technology -- Security measures; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Electronic data processing departments -- Security measures; Electronic books